2006
DOI: 10.1177/1078345806287773
|View full text |Cite
|
Sign up to set email alerts
|

Juveniles in Detention: How Do Girls Differ From Boys?

Abstract: The number of adolescents involved in the juvenile justice system is increasing dramatically, particularly among female juveniles. Little is known about the extent to which findings from research conducted on male delinquents can be generalized to females. This study was a preliminary examination of the self-reported risk factors of juveniles in detention to examine differences in self-reported risk factors by gender. Data were collected from a consecutive sample of 256 adolescents being held in an urban juven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…Aside from the research usefulness of ACASI, because studies have suggested that participants may report more honestly with ACASI (Hewett et al, 2003;Renker & Tonkin, 2007;Turner et al, 1996), it could be quite useful clinically, especially in detention settings where risk profiles are typically high. The rate of reported physical abuse (25.7%) and sexual abuse (11.4%) in our study is outside the range of estimates for physical abuse (57-81%) (Acoca & Dedel, 1998;Belknap & Holsinger, 2006;Chamberlain & Moore, 2002;Ryder, 2007;Simkins et al, 2004) and sexual abuse (25-67%) (Abrantes, Hoffman, & Anton, 2005;Acoca & Dedel, 1998;Alemagno et al, 2006;Belknap & Holsinger, 2006;Chamberlain & Moore, 2002;Dembo, Williams, & Schmeidler, 1993;Goodkind, Ruffolo, Bybee, & Sarri, 2009;Gover, 2004;Lederman et al, 2004;Ruffolo, Sarri, & Goodkind, 2004;Simkins et al, 2004) reported by justiceinvolved girls. The ACASI technology may have contributed to these lower rates.…”
Section: Refusalscontrasting
confidence: 61%
See 1 more Smart Citation
“…Aside from the research usefulness of ACASI, because studies have suggested that participants may report more honestly with ACASI (Hewett et al, 2003;Renker & Tonkin, 2007;Turner et al, 1996), it could be quite useful clinically, especially in detention settings where risk profiles are typically high. The rate of reported physical abuse (25.7%) and sexual abuse (11.4%) in our study is outside the range of estimates for physical abuse (57-81%) (Acoca & Dedel, 1998;Belknap & Holsinger, 2006;Chamberlain & Moore, 2002;Ryder, 2007;Simkins et al, 2004) and sexual abuse (25-67%) (Abrantes, Hoffman, & Anton, 2005;Acoca & Dedel, 1998;Alemagno et al, 2006;Belknap & Holsinger, 2006;Chamberlain & Moore, 2002;Dembo, Williams, & Schmeidler, 1993;Goodkind, Ruffolo, Bybee, & Sarri, 2009;Gover, 2004;Lederman et al, 2004;Ruffolo, Sarri, & Goodkind, 2004;Simkins et al, 2004) reported by justiceinvolved girls. The ACASI technology may have contributed to these lower rates.…”
Section: Refusalscontrasting
confidence: 61%
“…lifetime prevalence vs. recent or early childhood maltreatment), definitions of abuse used, and participant samples. Chamberlain and Moore (2002) assessed physical abuse directly, while Alemagno et al (2006) measured arguments or threats in the home. Regarding sample selection, rates of abuse among girls recommended for placement have limited comparability to girls in detention, as girls who are deeper in the system (i.e.…”
Section: Frequencies Of Maltreatment: a Comparative Perspectivementioning
confidence: 99%
“…Concerning differences in the definition of the threshold, previous studies based their conclusions about sex different thresholds on risk levels of delinquent boys and girls (Alemagno et al 2006; Belknap and Holsinger 2006; Emeka and Sorensen 2009; Johansson and Kempf-Leonard 2009; Van der Laan and Van der Schans 2010), whereas the current study identified the location of the threshold. Because delinquent girls had on average higher risk levels than boys and because delinquency is less prevalent in girls, previous studies concluded that girls have a higher threshold for delinquency.…”
Section: Discussionmentioning
confidence: 65%
“…Due to this amplification, delinquent girls would—even with a same delinquency threshold—have higher average risk levels than boys. Therefore, previous studies that focused on the average risk level for boys and girls found higher risk levels among delinquent girls than among delinquent boys (Alemagno et al 2006; Van der Laan and Van der Schans 2010). …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation